2019
DOI: 10.1021/acschemneuro.8b00383
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-Synuclein in Peripheral Tissues in Parkinson’s Disease

Abstract: Parkinson’s disease (PD) is a common neurodegenerative disorder. To date, the diagnosis of PD relies mainly on clinical manifestations whereas neuropathological confirmation of the brain is only possible with postmortem studies. Neuronal loss in the substantia nigra pars compacta (SNc) associated with Lewy bodies/neurites is the pathological hallmark feature of PD. The major component of Lewy pathology (LP) is misfolded alpha-synuclein (α-SYN). There is evidence that the distribution of LP is not only limited … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 121 publications
(245 reference statements)
1
36
0
Order By: Relevance
“…The pathogenesis of PD has been speculated to be associated with the GI tract as α-synuclein deposition was observed in the peripheral nervous system, especially in the enteric and pelvic plexus, of patients with PD [132]. A subsequent study suggested that the PD pathology originates from the peripheral organs in which α-synuclein is seeded, such as the GI tract and nasal cavity, before being retrograde transported to the cerebral cortex through the vagal nerve [132,133]. Furthermore, many patients with PD experience hyposmia and GI problems prior to the manifestation of classical PD symptoms, and patients with inflammatory bowel disease are also at a higher risk of developing PD [134].…”
Section: Gut Microbiota and Pdmentioning
confidence: 99%
“…The pathogenesis of PD has been speculated to be associated with the GI tract as α-synuclein deposition was observed in the peripheral nervous system, especially in the enteric and pelvic plexus, of patients with PD [132]. A subsequent study suggested that the PD pathology originates from the peripheral organs in which α-synuclein is seeded, such as the GI tract and nasal cavity, before being retrograde transported to the cerebral cortex through the vagal nerve [132,133]. Furthermore, many patients with PD experience hyposmia and GI problems prior to the manifestation of classical PD symptoms, and patients with inflammatory bowel disease are also at a higher risk of developing PD [134].…”
Section: Gut Microbiota and Pdmentioning
confidence: 99%
“…Abnormal α-syn aggregates have been demonstrated in various peripheral tissues, including the skin, salivary glands, adrenal glands, heart, retina, olfactory mucosa, and gastrointestinal tract [12,13]. Peripheral α-syn pathology may precede widespread central disease and thus potentially account for prodromal symptoms of PD (dysautonomia, including hypo-or hyperhidrosis, constipation, orthostatic hypotension, urinary and erectile dysfunction, anosmia etc.)…”
Section: Diagnosis Of Parkinson's Diseasementioning
confidence: 99%
“…transdermal patches, subcutaneous injection, percutaneous endoscopic gastrostomy for levodopa/carbidopa intestinal gel, and implantation of hardware in deep brain stimulation [DBS]). α-synuclein (α-syn), which plays a central role in PD pathogenesis [11], has been demonstrated over the past few decades to be present in multiple peripheral tissues, including skin [12,13]. This small protein (140 amino acids), involved in a variety of cellular mechanisms, undergoes misfolding and aggregation in the brain as well as in the skin [14], and may contribute to some non-motor symptoms [15].…”
Section: Introductionmentioning
confidence: 99%
“…The challenge is still the discrimination of patients and controls utilizing GIT-derived samples and an aSyn specific detection system. From a clinical but also cell-biological and biochemical view there are some arguments that favor GIT-specimens (especially from the colon) over other described sources as e.g., skin or blood (Fayyad et al, 2019;Ma et al, 2019). Interestingly, mice overexpressing human aSyn in neuronal cells (CNS and ENS), exhibit intestinal dysfunction besides the motor impairments (Chesselet et al, 2012).…”
Section: Structural Aspects Of Asyn Pathologymentioning
confidence: 99%